Barriers to e-customs in an emerging economy - Salehi, Mahdi (Management, 2012)
E-government is in fashion because of a lot of benefits which it can forgive to every society. One of the sub-systems of E-government is E-customs. So far, a lot of countries around the world have adopted E-customs in their own countries. One of the very latest countries in this area is Iran. The results of this study show that for the implementation of E-customs there are several barriers which should be removed as early as possible in the very near future.
Keywords: carine; državna uprava; efficiency; elektronsko poslovanje; Iran; učinkovitost